(untitled) (CIPEEX, 2023)
The assessment of the functional autonomy of the elderly aims to determine their ability to take care of themselves, perform basic and instrumental daily living activities, as well as analyze how they behave in the environment they live in. This study aims to analyze the levels of functional autonomy of elderly individuals in a long-term care institution (ILPI) in the municipality of Rio Verde - GO. The study consists of a cross-sectional quantitative analysis of secondary data, where sociodemographic and economic aspects, general health, institutionalization, and functional autonomy (Functional Autonomy Measurement System) were evaluated. Those elderly individuals who were over 60 years old and had been institutionalized for more than six months at the time of data collection were included in the study. Seventy-five elderly individuals met the inclusion criteria. The participants had an average age of 76.3±8.0 years, and the majority were male (n=54; 72.0%), between 60 and 79 years old (n=52; 69.3%), without a partner (n=57; 76.0%), without formal education (n=50; 64.0%), retired (n=68; 90.7%), using more than 5 medications (n=41; 54.7%), and having more than 3 comorbidities (n=63; 84.0%). It was found that 28.0% of the evaluated elderly presented as dependent, representing the lowest level of functional autonomy, indicating significant challenges for maintaining independence and quality of life, such as specific interventions like rehabilitation programs, exercises, and environments that encourage independence.